Stable expression of bacterial transporter ArsB attached to SNARE molecule enhances arsenic accumulation in Arabidopsis. (1st November 2020) - Deromachi, Yusuke; Uraguchi, Shimpei; Kiyono, Masako; Kuga, Kazuhiro; Nishimura, Kohji; Sato, Masa H.; Hirano, Tomoko
ABSTRACT: Acute and chronic arsenic (As) toxicity is a global health issue affecting millions of people, which leads to inactivation of over 200 enzymes, particularly those involved in cellular energy pathways and DNA synthesis and repair. The fern Pteris vittata acts as a hyperaccumulator of As and may be useful for phytoremediation to reduce disposal risks by utilizing metal-enriched plant biomass in energy and metal recovery. However, these ferns grow in limited environments and its transplantation and transport can be challenging. Therefore, we generated a transgenic Arabidopsis plant as a seed plant model, capable of accumulating As in their vacuole lumen. This was achieved by transforming the As-resistant bacterial As transporter, ArsB, via fusion with a organelle-targeting signal to the vacuolar membrane, N-ethyl-maleimide-sensitive factor attachment protein receptors (SNAREs) protein, VAMP711. In this study, we developed the iVenus assay as a method for detecting whether the N- or C-terminus of a membrane protein is located on the cytoplasmic or exoplasmic side, and from the result of the iVenus assay, we generated the transgenic plant introduced N-terminal end of ArsB with VAMP711, localized to the central vacuolar membrane to accumulate As in the shoot and differentiation zone of root.